Transient suppression of Wnt signaling in poor-quality buffalo oocytes improves their developmental competence - Ahuja, Kriti; Batra, Vipul; Kumar, Rakesh; Datta, Tirtha Kumar (Frontiers in Veterinary Science, 2024)
Introduction One of the most evolutionary conserved communication systems, the Wnt signaling pathway is a major gene regulatory pathway that affects the developmental competence of oocytes and regulates most embryonic developmental processes. The present study was undertaken to modulate the canonical Wnt (Wingless/integration) signaling pathway in the poor-quality (colorless cytoplasm after Brilliant Cresyl Blue staining, BCB-) buffalo cumulus-oocyte complexes (COCs) to improve their in vitro maturation (IVM) and embryo production (IVEP) rates. Methods The expression of key Wnt pathway genes was initially assessed in the good (blue cytoplasm after Brilliant Cresyl Blue staining, BCB+) and poor quality (BCB-) buffalo COCs to establish a differential activity of the Wnt pathway. The BCB- COCs were supplemented with the Wnt pathway inhibitor, Dickkopf-related protein 1 (DKK1) and later subjected to IVM and IVEP along with the BCB+ and BCB- controls. The cumulus expansion index (CEI), rate of nuclear maturation (mean percentage of oocytes in the MII stage) and embryo production, and the expression of developmentally important genes were evaluated to assess the effect of Wnt pathway inhibition on the development competence of these poor-quality oocytes. Results The Wnt pathway genes exhibited a significantly higher expression (p < 0.05) in the poor-quality BCB- oocytes compared to the good-quality BCB+ oocytes during the early maturation stages. The supplementation of BCB- COCs with 100 ng/mL DKK1 effectively inhibited the expression of the key mediators of the Wnt pathway (β-catenin and dishevelled homolog 1, DVL1). DKK1 supplemented BCB- COCs exhibited significantly improved cytoplasmic and nuclear maturation indices, development rates and significantly elevated expression (p < 0.05) of genes implicated in germinal vesicle breakdown (GVBD) and embryonic genome activation (EGA) vis-à-vis BCB- control COCs. Conclusion These data indicate that inhibition of the Wnt pathway during the initial course of oocyte maturation can improve the development competence of poor-quality buffalo oocytes.